Medical Waste in the Light of Current Legal Regulations - Frańczuk, Magdalena (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Medical waste can be one of the most serious threats to human life and health, especially due to the risk of infections (bacteria and viruses), the presence of hazardous chemicals, and microbiological cultures. Recycling and disposing of this waste is problematic, and is subject to a separate set of laws. The position and responsibilities of those responsible for the management of medical waste are also unique. The study focuses on the definition of medical waste (excluding veterinary waste). It shows the most important problems in this area and how it should be managed given the current legal regulations. Statistics and issues related to the control of medical waste management in Poland are cited.